Analisis Dampak Penggunaan Internet Terhadap Minat Belajar Mahasiswa : Studi Kasus : Institut Teknologi Del - Melisa Septiani Togatorop; Mariana Simanjuntak (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2024)
Institut Teknologi Del (IT Del) is a technological-focused institution of higher education located in Sitoluama, North Sumatra. Emphasizing innovation in technology, IT Del is an ideal setting to explore the impact of internet usage on the learning process. This study aims to examine the influence of internet usage on student learning interest at IT Del. Using the Theory of Reasoned Action (TRA) as a theoretical framework, the research investigates the relationship between attitudes toward internet usage and social influence on learning interest. Data were collected through an online survey from 50 IT Del students. Multiple regression analysis indicates that both attitudes toward internet usage and social influence have a significant positive impact on student learning interest. The research findings reveal that 44.2% of the variation in learning interest can be explained by these independent variables. These findings underscore the importance of integrating internet technology in educational strategies and the significant role of academic social environments in enhancing student learning interest. This study provides valuable insights for IT Del and other higher education institutions in designing effective learning policies and practices in the digital era.